IMPLEMENTASI PEMBELAJARAN BAHASA ARAB MODEL CONTEXTUAL TEACHING AND LEARNING DENGAN MEDIA EDUCAPLAY - Mahbubillah, Ilman; Hasaniyah, Nur; Al Anshory, Abdul Muntaqim; Abidin, Munirul Zainal (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to assess the effectiveness of the Contextual Teaching and Learning (CTL) approach integrated with the Educaplay platform in enhancing students’ academic performance in Arabic language learning at SMP Insan Amanah Malang. A quantitative method was employed using a quasi-experimental design with a non-equivalent control group. The research subjects consisted of all seventh-grade students, specifically classes VII-A and VII-B. Class VII-A was designated as the experimental group receiving the intervention, while class VII-B served as the control group. Data were collected through observations and written assessments to measure Arabic learning outcomes in both groups. The data analysis involved prerequisite tests and hypothesis testing. The findings revealed a significant impact of implementing the CTL model supported by Educaplay on students’ academic achievement. This was confirmed by the hypothesis test result, showing an Asymp Sig (2-tailed) value of 0.019, which is below the 0.05 significance threshold. Consequently, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Descriptive statistical analysis showed that the average pre-test score for the experimental group was 73.8462, while the control group scored 74.2308. After the intervention, the experimental group's average score increased to 86.1538, whereas the control group reached only 75. This discrepancy highlights the superior academic performance of students who received the specialized treatment. Based on this evidence, it can be concluded that integrating the CTL approach with the interactive Educaplay media contributes positively to improving students’ Arabic learning outcomes. ABSTRAKPenelitian ini bertujuan untuk menilai sejauh mana pendekatan Contextual Teaching and Learning (CTL) yang dipadukan dengan platform Educaplay dapat meningkatkan prestasi akademik siswa dalam pembelajaran bahasa Arab di SMP Insan Amanah Malang. Studi ini menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimen dan model kelompok kontrol non-ekuivalen. Subjek penelitian terdiri dari seluruh siswa kelas VII, yaitu kelas VII-A dan VII-B. Kelas VII-A ditetapkan sebagai kelompok eksperimen yang mendapatkan perlakuan, sementara kelas VII-B berperan sebagai kelompok kontrol. Teknik pengumpulan data mencakup observasi serta tes tertulis untuk menilai hasil belajar bahasa Arab di kedua kelompok. Data dianalisis melalui uji prasyarat dan pengujian hipotesis. Hasil penelitian menunjukkan bahwa penerapan model CTL yang didukung oleh Educaplay berdampak signifikan terhadap peningkatan prestasi belajar siswa. Hal ini dibuktikan melalui uji hipotesis yang menghasilkan nilai Asymp. Sig (2-tailed) sebesar 0,001, lebih kecil dari nilai signifikansi 0,05, sehingga hipotesis nol (Ho) ditolak dan hipotesis alternatif (Ha) diterima. Berdasarkan analisis statistik deskriptif, rata-rata skor pretes siswa di kelompok eksperimen adalah 65,09, sementara kelompok kontrol memperoleh skor 70,90. Setelah perlakuan, skor rata-rata kelompok eksperimen meningkat menjadi 84,31, sedangkan kelompok kontrol hanya mencapai 73,43. Perbedaan ini menegaskan bahwa siswa yang memperoleh pembelajaran dengan CTL dan Educaplay menunjukkan hasil akademik yang lebih baik. Oleh karena itu, dapat disimpulkan bahwa penggabungan pendekatan CTL dengan media interaktif Educaplay memberikan dampak positif terhadap peningkatan hasil belajar bahasa Arab siswa.